Workshop addressing sexuality and dating directed to adolescents - Levandowski, Daniela Centenaro; Schmidt, Márcia Moura (Paidéia (Ribeirão Preto), 2010)
This paper reports activities carried out in workshops addressing sexuality and dating directed to adolescent students of public schools in Caxias do Sul/RS, Brazil included in the program Comunitário Cidadão do Século XXI [21st Century Citizen Community]. These workshops aimed to enable the exchange of experiences and reflection about sexuality-related actions and choices. The meetings were organized with a ludic approach, through group dynamics and directed activities such as reading and discussions on texts and movies, addressing several themes. The need to implement preventive actions to reduce psychosocial risk factors, giving these individuals opportunities to achieve healthy development is highlighted.